With data, educate yourself and start simple - Gil, Jodie Mozdzer (The Quill, 2015)
The data sets have a variety of content, including farmers market locations, school absentee rates and crime statistics. START SIMPLE The downloadable data can be as simple as a spreadsheet chronicling one data point over time - for example, the amount of money the federal government has spent on school food programs since 1969.
Num Pages: 1 Place: Indianapolis, United States
Keywords: Criminal statistics; Databases; Datasets; Digital broadcasting; Journalism; Journalists; Trends; dept.jrn

Choosey journalists choose GIFs - Gil, Jodie Mozdzer (The Quill, 2016)
The still photographs incorporate subtle movement, such as wind blowing grass or eyes blinking, that play on repeat through an animated GIF. [...]don't make your readers seasick with too much movement or too many GIFs on the same page.t
Num Pages: 1 Place: Indianapolis, United States
Keywords: Digital broadcasting; Photographs; School districts; Software reviews; Video recordings; dept.jrn

The Power of Free Expression in America - Harris, Frank (Cognella Academic Publishing, 2016)
Keywords: Freedom of expression; United States; dept.jrn; faculty_collection

The Craft of Quoting: The Art of Writing It Like It's Said - Harris, Frank (Cognella, Inc., 2016)
The Craft of Quoting helps student-writers develop the ability to use quotes in such a way that their readers "hear" and "feel" what the speaker is saying and understand its relevance to the topic at hand. Students will learn how to write quotes with style, clarity, and consistency. The book provides clear guidelines for mechanical correctness, appropriate attribution, and paraphrasing. The use of paragraph breaks for stylistic purposes is also addressed. In addition, The Craft of Quoting sets out twelve "quote-nots" that help students avoid the common pitfalls of using quotes in written work, as well as nine essential quote patterns that enhance efficacy and impact. The Craft of Quoting also addresses the importance of ethics in writing, especially as these relate to plagiarism and academic dishonesty. Practical and concise, The Craft of Quoting is ideally suited to journalism students whose reporting involves interviewing sources. It is also an excellent tool for second-tier writing classes in which students explore other people's thoughts and feelings in their work.
Keywords: Handbooks; manuals; etc; Journalism; dept.jrn; faculty_collection

Local authors can be friends - Froetschel, Susan (Library Journal, 2010)
tex.unique-id: ISI:000274606200018
Keywords: dept.jrn; ⛔ No DOI found

Tracing home address exemptions in state FOI laws - Gil, Jodie (The Journal of Civic Information, 2019)
Privacy concerns have prompted many states to close off once-public information from release through the freedom of information process. This study looks at the personal privacy exemptions for home addresses in 50 states and Washington, D.C., in both 2011 and 2019. There were 16 instances of a change in state law during that time – only three toward more transparency. Voter registration records were the most open of the three categories reviewed, with more than half the states requiring disclosure of home addresses in 2019. This study can help guide journalists, policy makers and records holders as they navigate proposed changes to FOI laws.
0 citations (Crossref) [2023-10-31]
Keywords: dept.jrn; peer-reviewed